THE STRUCTURE AND DYNAMICS OF THE MANTLE WEDGE - van Keken P.E. (My University, 2003)
A large amount of water is brought into the Earth’s mantle at subduction zones. Upon subduction, water is released from the subducting slab in a series of metamorphic reactions. The resulting flux into the mantle wedge modifies its chemical and physical properties by mineral hydration with associated weakening, flux melting and changes in the dynamics and thermal structure of subduction zones. Water guides the formation of volcanoes, earthquakes, continent formation and the long-term chemical evolution of the Earth’s mantle. Recent observational advances include the better documentation of the role of water in causing melting from minor and trace elements in arc lavas, improved structure of the mantle wedge derived from seismic tomography, and documentation of hydration of the mantle wedge from converted phases. High-pressure experiments allow for a quantification of the role of water on seismic velocities and attenuation and rheological changes, which provide essential input into models of subduction zones. Computational models provide additional evidence for the importance of the mantle wedge in subduction zone dynamics.